A systematic review of sport-based adolescent mental health awareness programmes - Sullivan, N.; Breslin, G.; McLaughlin, M.; Shannon, S.; Leavey, G.; Dempster, M. (PLOS ONE, 2025)
Background Adolescent mental illness is of increasing concern, with a high prevalence in many parts of the world. Early engagement, detection and receiving support are warranted to reduce the severity of symptoms. Increasing mental health literacy (MHL) through sport to adolescents is one way of engaging young people and signposting them to services. The aim of this systematic review was to identify the effect of interventions, risk of bias, and theoretical application in sport-based adolescent mental health awareness programmes.